Coordinated Attitude Control for Synthetic Aperture Radar Satellites with Quantization and Communication Delay - Fu, Jingbo; Liu, Ming; Li, Huayi; Cao, Xibin (International journal of control, automation, and systems, 2019)
This paper studies the coordinated attitude control problem of synthetic aperture radar satellites and proposes two types of terminal sliding mode control schemes. The first control law is investigated based on the conventional non-singular terminal sliding mode approach and modified Rodrigues parameters with the consideration of signal quantization and communication delay. Based on the first control scheme, we develop the second control method with an integral-based event triggering condition to reduce the updating frequency of the control command from controllers to actuators. Finally, numerical simulation examples based on a cluster of three satellites are presented to show the effectiveness of the proposed two designed control methods.